Proline metabolism and transport in plant development - Lehmann, Silke; Funck, Dietmar; Szabados, László; Rentsch, Doris (Amino acids, 2010)
Proline fulfils diverse functions in plants. As amino acid it is a structural component of proteins, but it also plays a role as compatible solute under environmental stress conditions. Proline metabolism involves several subcellular compartments and contributes to the redox balance of the cell. Proline synthesis has been associated with tissues undergoing rapid cell divisions, such as shoot apical meristems, and appears to be involved in floral transition and embryo development. High levels of proline can be found in pollen and seeds, where it serves as compatible solute, protecting cellular structures during dehydration. The proline concentrations of cells, tissues and plant organs are regulated by the interplay of biosynthesis, degradation and intra- as well as intercellular transport processes. Among the proline transport proteins characterized so far, both general amino acid permeases and selective compatible solute transporters were identified, reflecting the versatile role of proline under stress and non-stress situations. The review summarizes our current knowledge on proline metabolism and transport in view of plant development, discussing regulatory aspects such as the influence of metabolites and hormones. Additional information from animals, fungi and bacteria is included, showing similarities and differences to proline metabolism and transport in plants.